Selective oxidation of glycerol over titania supported AuPd bimetallic catalysts - Ainol Hayah, Ahmad Nadzri; Noraini, Hamzah; Aznira, Alias; Jumat, Salimon; Mohd Ambar, Yarmo (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.